Strategies for early detection of psychopathologies in candidates for post-bariatric plastic surgery - Daniel Nunes E Silva; Marcelo Rosseto; Kleber Francisco Meneghel Vargas; Agliberto Augusto Barsaglini Marcondes Rezende; Evelyn Gaspar Balbino; Thaisa Richards de Andrade; Heytor Jóse de Oliveira Cabral (Revista Brasileira de Cirurgia Plástica)
Introduction: The increase in demand for post-bariatric plastic surgery has revealed a high prevalence of psychopathologies in patients undergoing the procedure, requiring the need to diagnose these diseases in the preoperative period. The use of specific psychological screening tools has been promoted; however, a gold-standard method has not yet been fully established. Objective: To carry out a review of the literature for alternatives available for the preliminary psychological evaluation of patients who are candidates for post-bariatric plastic surgery, presenting the method recommended in the Post-Bariatric Plastic Surgery outpatient clinic of the Federal University of Mato Grosso do Sul (UFMS). Methods: We reviewed the clinical trials which employed psychological screening tools preoperatively in patients who were candidates for post-bariatric plastic surgery; the MEDLINE/PubMed database was searched using keywords such as “bariatric surgery”, “body image”, “quality of life”, “obesity”, “plastic surgery” and “psychiatry”, for clinical trials published in the last 20 years. Herein, we discuss the findings and analyze the most common methodologies used. Results: Only four clinical trials used psychopathology screening tools in postbariatric plastic surgeries preoperatively, and one method could not be identified. Conclusion: The use of appropriate strategies to screen for psychopathologies helps prevent significant losses in the postoperative period, but the tools still lack validation in the post-bariatric population. Besides possessing extensive clinical-surgical technical knowledge, the plastic surgeon must remain attentive to the signs and psychopathological symptoms in these patients, referring them for psychological and psychiatric evaluation when indicated.